SGHOSTI - sistema de informação gerencial para um hotel de pequeno porte no Município de Itacoatiara - Serudo, Rodrigo dos Santos (Brasil, 2020)
Nowadays, with technological advances evolving its guidelines, the world market also needs this monitoring to be adequate to the paradigm changes in our society. However, it is also necessary for the companies that compose it to evolve their business methodologies if they want to maintain a content of success in this aggressive and competitive market, given that it will always be subject to changes. Large, medium and small companies need to be duly attentive and prepared for these changes in their scope of work, because in the world where there is competition from both sides, the one who keeps their model of business will always be the most prominent in the market. updated management. In view of this, it is necessary to stress the importance of managerial Information Systems that directly impact these companies that aim at the differential in the market. Based on this principle, the idea arose to develop an information system that manages and assists in the business development of a small company in the service sector in the city of Itacoatiara, bringing about new positive changes within the local market. The methodology consists, firstly, of a bibliographic survey to compose the theoretical foundation and define an initial proposal, where the construction of the software will be carried out, based on the Spiral Model, which includes the requirements survey, definition of the documentation, as well as the implementation of the software. And finally, the implementation of the system in the company and the performance of usability tests, since it is expected to obtain a positive evaluation of the software by its users.